A Method for Evaluating the Peripherality of Rural Settlement Units Based on the Principles of Spatial Order and Sustainable Development - Tomasz Podciborski; Iwona Krzywnicka (Barometr Regionalny, 2015)
The objective of this study was to propose a method for evaluating the peripherality of rural settlement units based on the principles of spatial order and sustainable development. Detailed goals involved the determination of evaluation indicators, a scoring system and evaluation principles based on the results of a questionnaire survey. The proposed method was verified on the example of three survey sites.